Schatten-von Neumann properties of bilinear Hankel forms of higher weights - Sundhäll, Marcus (MATHEMATICA SCANDINAVICA, 2006)
Hankel forms of higher weights, on weighted Bergman spaces in the unit ball of C^d, were introduced by Peetre. Each Hankel form corresponds to a vector-valued holomorphic function, called the symbol of the form. In this paper we characterize bounded, compact and Schatten-von Neumann S_p class (2≤ p<∞) Hankel forms in terms of the membership of the symbols in certain Besov spaces.